Data-Driven Human Modeling by Sparse Representation. (November 2020) - Wu, Yiu-Bun; Liu, Bin; Liu, Xiuping; Wang, Charlie C.L.
Abstract: Data-driven methods for modeling the realistic shapeof 3D human bodies need to access datasets that contain a large amount of 3D human models. We develop a method based on sparse representation in this paper to represent 3D human models as signals of patches. Unlike the general mesh compression approaches, all mesh models used in a data-driven human modeling framework have the same mesh connectivity. By using this property, we segment a human model into patches containing the same number of vertices. L 0 -learning algorithm is selected to train an overcomplete dictionary matrix, which in turn introduces sparse representation of the dataset. Patch signals of individual human models can then be extracted by using the dictionary matrix. With the ease of balance control between sparsity and accuracy that is featured by the chosen learning algorithm, a representation with high compression ratio and low shape-approximation error can be determined. The results have been compared with the widely used statistic representation based on principal component analysis (PCA) to verify the effectiveness of our approach. Moreover, the method for using sparse representation in the regression-based statistical modeling of 3D human models has been presented at the end of the paper. Graphical abstract: Highlights: A sparse representation method for 3D human models with less memory consumption. A method of constructing patch signals for generating a large amount of samples. A controllable level of compression with higher accuracy in data-driven modeling.